Roman settlement in the Maghreb During the first three centuries AD (an analytical historical study) - Hasanain Abdulrazzaq Hasan Hadi Alhadi (مجلة كلية التربية للبنات)
The countries of the Maghreb were characterized by a set of economic, geographical and political characteristics, which qualified them and raised their status, until they made them the focus of the ambitions of the great powers that sought to control them and dominate the countries of the Mediterranean basin during classical times.